2003
DOI: 10.1080/00365540310008041
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies in Mother's Milk Protect Children Against Giardiasis

Abstract: The protective effect of anti-Giardia antibodies in mother's milk on the acquisition of Giardia infection in their children during the first 2 y of life was analysed as part of a prospective study on infant diarrhoea in a group of 307 mothers and children in Leòn, Nicaragua. Among 24 children acquiring infection within the first 6 months, 23 were born to mothers lacking antibodies. These children also developed more severe diarrhoea. A significant difference between children born to mothers with and without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 6 publications
1
18
1
1
Order By: Relevance
“…Chronic, asymptomatic or mildly symptomatic infections may persist for months or even years in the presence of circulating antibodies (Faubert 2000). The mechanism of protection afforded by maternal antibody, other non-specific factors in milk, and relative protection from the environment for breast-fed infants is a matter of debate (Miotti et al 1986;Nayak et al 1987;Sterling et al 1991;Zu et al 1992;Walterspeil et al 1994;Tellez et al 2003). Some have shown significant benefit while others have suggested that other non-specific mechanisms might be equally important.…”
Section: Serological Study Reportsmentioning
confidence: 99%
“…Chronic, asymptomatic or mildly symptomatic infections may persist for months or even years in the presence of circulating antibodies (Faubert 2000). The mechanism of protection afforded by maternal antibody, other non-specific factors in milk, and relative protection from the environment for breast-fed infants is a matter of debate (Miotti et al 1986;Nayak et al 1987;Sterling et al 1991;Zu et al 1992;Walterspeil et al 1994;Tellez et al 2003). Some have shown significant benefit while others have suggested that other non-specific mechanisms might be equally important.…”
Section: Serological Study Reportsmentioning
confidence: 99%
“…On the other hand, the weaner calves of over 7 months old might have been exposed to the parasite in the field, and might have developed the anti-Besnoitia antibodies, since the maternal immunity should have waned at that age to very low levels. It's a known fact that neonatal B-cells could produce IgM and limited amounts of IgG subclasses, the levels of which could rise slowly to reach adult levels for IgG 1 and IgG 3 at the age of 12 months in humans (Tellez et al, 2003). In conclusion, there was a high prevalence of antibodies to B. besnoiti in sera and milk which suggests that the parasite is endemic among cattle in the surveyed Northern States of Nigeria.…”
Section: Discussionmentioning
confidence: 76%
“…The antibodies might have been passed to these calves through suckling of colostrum. It has been established that biologically stable IgA and IgM could be transferred to infants through natural milk for protection against several disease agents including protozoa (Lawrence & Pane, 2007) and could confer solid immunity to new born humans (Tellez et al, 2003) and animals (O'Handley et al, 2003). The presence of antibodies to B. besnoiti in sera from calves at the dilution of 1:256, observed here, is in tandem with an established record (Shkap et al, 1994) in which the new born calves in Israel had antibody titers ranging from 1:64 to 1:1024.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxic effects of these products can be reverted in vitro by addition of bovine serum albumin or human duodenal-jejunal mucus most likely due to trapping of the toxic compounds [30]. Epidemiological studies reveal a correlation between protection from symptomatic giardiasis in newborn children with breastfeeding, and this has been attributed to the occurrence of G. duodenalis-specific antibodies (mainly sIgA) in the milk of the mothers [31][32][33][34]. But, milk from non-infected mothers was also shown to kill parasites in vitro which was linked to toxic products of lipolysis too [35,36].…”
Section: Natural Resistance Mechanismsmentioning
confidence: 97%